The Effect of the CTL Learning Model on the Learning Outcomes of Magnetic, Electrical, and Technology Science Science at SDN 3 Dongko - Pratiwi, Gita; Setyawan, Agung; Kusumawati, Intan (Citra Dharma Cindekia, 2025)
This research aims to determine the effect of the Contextual Teaching and Learning (CTL) learning model on science and social learning outcomes regarding magnetism, electricity and technology in class V students at SDN 3 Dongko. This research is quantitative research with an experimental type of research, the design used is Pre-Experimental Design with One Grup Pretest Posttest. Sampling used random sampling technique. The sample used was 20 experimental class students. Data was collected using pre-test and post-test questions. The research results show that the contextual teaching and learning (CTL) learning model has a significant influence on student learning outcomes. The magnitude of the difference is proven by the results of the paired sample t test. The results of the paired sample t-test calculations obtained a significance value of 0.000. Based on the test criteria if the Sig.2.093) then H0 is rejected and Ha is accepted, which means there is an influence significant in the application of the contextual teaching and learning (CTL) learning model on science and social learning outcomes of magnetism, electricity and technology material in class V students at SDN 3 Dongko.